Our Numbered Days - Hilborn, Neil (Minneapolis, Minnesota Button Poetry / Exploding Pinecone Press, 2015)
"While this collection ruminates on love, heartbreak, and mental illness, these poems are anything but saccharine. Hilborn uses the same humor and self-deprecation that propelled "OCD" to success in order to make his unmatched vulnerability all the more powerful. Ultimately, Hilborn is a poet of the people: his work is accessible, honest, and entertaining a revitalizing entry in contemporary poetry"--Amazon.com.
Keywords: First Loves -- Poetry; Man-women relationships -- Poetry; American Poetry -- 21st Century